Determination of the Optimal Formulation of Goroho Banana and Gedi Leaf Composite Flour Based on Antioxidant Activity and Physicochemical Properties - Mercy I R Taroreh; Edi Suryanto; Thelma D.J. Tuju (Postgraduate, University of Mataram, 2025)
Goroho bananas (Musa acuminata L.) and gedi leaves (Abelmoschus manihot L.) have potential as functional foods due to their antioxidant content and nutritional properties. However, the use of these two ingredients in the form of composite flour and the determination of the optimal formulation to produce high antioxidant activity while maintaining acceptable physicochemical characteristics are still limited. This study aims to determine the optimal formulation of gedi leaf and goroho banana composite flour based on antioxidant activity and physicochemical properties. The study used a completely randomized design (CRD) with three replicates, consisting of five treatments, namely single gedi leaf flour, gedi leaf:goroho banana ratios of 75:25, 50:50, and 25:75, and single goroho banana flour. Antioxidant activity was analyzed by measuring total phenolic compound (TPC) content and DPPH free radical scavenging ability, while physicochemical characteristics included moisture, ash, fat, protein, carbohydrate, and crude fiber content. The results showed that increasing the proportion of gedi leaf flour significantly increased the protein, fat, ash, fiber, total phenolic content, and antioxidant activity, while increasing the proportion of goroho banana flour increased the carbohydrate content. These findings indicate a compromise between antioxidant capacity and energy contribution in composite flour formulations. Based on the balance between antioxidant activity and nutritional composition, the 50:50 and 75:25 gedi leaf:goroho banana formulations were determined to be the optimal formulations. The results of this study indicate that both formulations have the potential as functional composite flours for the development of antioxidant-rich food products